Noise levels in the training center - Castro Gómez, Jennifer Julieth
The objective of this research is to determine the concentration of noise levels in the training ambients from the Technological Complex for Agribusiness Management in the municipality of Caucasia, through the technique of direct observation, using specialized equipment, such as the occupational sound level meter (Brand flus Model ET958), The most recommendable equipment for measuring the noise concentration levels in a given space. Seven training ambients susceptible to noise emissions were selected. Fifty minutes of measurements were taken during five days of the week, in the morning, afternoon and evening shifts. The results obtained during this research allowed to establish the maximum and minimum noise levels expressed in decibels of dB emitted in the studied training ambients, during the day of the week and the respective shift, comparing them with standardized permissible levels in the current legal regulations. The factors that can influence the concentrations above the permissible levels of noise in the training ambients, may be the use of audiovisual equipment, the tone of voice, the lack of recreational and sports spaces, as well as common areas and polyvalent ambients or what it is the same: shared ambients.